Forhue: an assistive mobile application for color - blind individuals using KNN algorithm. - Banez, Crystal Mae M., Poso, Raseck Kiel D., Tavas, Ella Micca B. 4 0 16; 5
u
Undergraduate Thesis (BS in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2